No such thing as a free ride: The impact of disability labels on relationship building at work. (April 2022) - Brzykcy, Anna; Boehm, Stephan
Do disability legislations that are meant to be beneficial for the employment situation of persons with disabilities have nevertheless unintended negative consequences? To provide key resources such as the right to workplace accommodation, governmental agencies first need to identify eligible persons and label them accordingly. However, this label may, in turn, induce public and self stigma that entails negative consequences for labeled individuals. We address this puzzle using a quasi-experimental study design: sharp regression discontinuity design. Specifically, we examine whether individuals officially labeled as "severely disabled" perceive fewer opportunities for relationship building at work than their counterparts with a similarly severe, yet unlabeled, disability condition. We use data from 845 employees with disabilities, which were drawn from a representative German workforce data set. As expected, labeling leads to perceptions of fewer opportunities for relationship building. We find this effect to be independent from supervisor knowledge of subordinate disability, type of disability, and one's visibility of disability. These robustness checks strengthen the argument that the labeling effect might be driven primarily by self stigma rather than public stigma. Implications for organizations and public authorities are discussed.